Pengaruh Dosis Pupuk Kandang Ayam terhadap Pertumbuhan dan Hasil Tiga Macam Varietas Selada (Lactuca sativa L.) - Dwi Ismawati; Tri Rahayu; Srie Juli Rachmawatie (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
The study aims to determine the influence of chicken manure dose on growth and yield on three kinds of lettuce (Lactuca sativa, L.) planted in a polybag. This research was conducted from November 2019 until January 2020, in Gerdu Village, Karangpandan District, Karanganyar Regency, between 450 - 650 m above sea level. The research used a factorial method with a Completely Randomized Design (CRD) consist of two treatment factors. The first factor is dose of chicken manure consisting of 3 levels (D1 = 62.5 g/ polybag, D2 = 125 g / polybag, D3 = 187.5 g/ polybag). The second factor was varieties of lettuce (V) consist of 3 types (V1 = Grand Rapids Variety, V2 = Kriebo Variety, V3 = Bisi SL 02 Variety). Analysis of variance was used to analyzed the data, with the F test at 5% and 1% levels and then followed by Duncan's multiple range test at 5% level. The results showed that chicken manure dosage significantly affects fresh weight and consumption weight per plant. The best dose of chicken manure for the treatment is 125 g / polybag. The varieties significantly affected plant height, fresh weight, and consumption weight and significantly affected leaf width per plant. The interaction between the dose of chicken manure and varieties of lettuce (DxV) showed the best results on the combination 125 g / polybag chicken manure dose with the Kriebo variety (D2V2). This treatment combination gives the highest consumption weight, which is 76.52 g. While the treatment combination of 62.5 g / polybag chicken manure dose and Bisi SL 02 variety (D1V3) had the lowest consumption weight (39.68 g).